Pengaruh Manajemen Sumber Daya Manusia, Budaya Organisasi dan Motivasi Terhadap Peningkatan Kinerja Polri di Polda Metro Jaya Jakarta - Yudhi Abdi Wijoyo; Muhamad Arief Noor; Joned Ceilendra Saksana (Indo Publishing, 2025)
Related to global environmental developments that significantly influence regional and national environments, the pace of development and the lives of Indonesian people has become increasingly dynamic. The rhythm of community activities in various fields is accelerating, as reflected in the increased mobility of people and goods, the exchange of information, and transactions, both economic and social. The quantity of crime is increasing, the intensity and variety of its methods are also increasing, and it has even become mixed with political, economic, and cultural nuances. The emergence of riots in various locations in recent times also accompanies the process of change in Indonesian society. All of these phenomena demand a greater role from the Indonesian National Police (Polri), as the leading element in handling Public Security and Order (Kamtibmas). The t-test showed that for the Human Resources Management variable, the calculated t value was 2.988 and the t table was 2.045. Therefore, since the calculated t value of 2.988 < the t table value of 2.045 and the significance value was 0.004 < 0.05, it can be concluded that Ho is rejected, meaning that Human Resources Management has a partial significant effect on Performance Improvement. Organizational Culture variable with tcount value of 3.140 and ttable of 3.140, because the tcount value of 3.140> ttable value of 2.045 and the significance value of 0.002 <0.05, it can be concluded that Ho is rejected, meaning that Organizational Culture partially has a significant effect on Performance Improvement. Motivation variable with tcount value of 4.835 and ttable of 2.045, because the tcount value of 4.835> ttable value of 2.045 and the significance value of 0.000 <0.05, it can be concluded that Ho is rejected, meaning that Motivation partially has a significant effect on Performance Improvement. The F-test revealed a calculated F value of 533.752 with an F-table of 3.35. Since the calculated t value of 533.752 is greater than the t-table value of 3.35, and the significance value is 0.000 <0.05, it can be concluded that Ho is rejected. This means that HR Management, Organizational Culture, and Motivation collectively have a significant effect on Performance Improvement. The R-value is 0.971, indicating a very strong relationship between the variables of HR Management, Organizational Culture, and Motivation and the improvement of Member Performance. Meanwhile, the R-Square value is 0.943, indicating that the independent variables, consisting of HR Management, Organizational Culture, and Motivation, contribute 0.943 or 94.3% to the improvement of POLRI performance, while the remainder is influenced by other factors not included in the model